2004
DOI: 10.1620/tjem.203.1
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Intraluminal Colonization by Antibiotic Lock in Catheters

Abstract: Antibiotic lock (AL) technique for catheter related infection encompasses the filling of a catheter lumen with high concentrations of antibiotics for hours. The goal of AL therapy is to decontaminate the intraluminal surface of the catheter. However the duration of antibiotic therapy is not established. An in vitro model was designed to establish the time needed to eliminate intraluminal microbial colonization and to evaluate the efficacy of vancomycin in comparison with teicoplanin by using laboratory AL mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(44 reference statements)
0
8
0
3
Order By: Relevance
“…Presently, at least 2 weeks of AL treatment is recommended for intraluminal catheter infection caused by virulent microorganisms. On the other hand, studies conducted by Oncu et al [6,24] displayed the efficiency of shorter AL therapy in catheters infected by staphylococci. However, studies investigating the optimal duration of antifungal lock therapy are missing in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Presently, at least 2 weeks of AL treatment is recommended for intraluminal catheter infection caused by virulent microorganisms. On the other hand, studies conducted by Oncu et al [6,24] displayed the efficiency of shorter AL therapy in catheters infected by staphylococci. However, studies investigating the optimal duration of antifungal lock therapy are missing in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…In current guidelines, CVC removal is considered as an integral part of the therapeutic approach to CRI caused by fungi [3]. However, removal of a CVC, particularly a tunneled CVC used for long-term catheterization in a critically ill patient, is associated with significant practical problems and cost [5,6]. It is assumed that a conservative treatment strategy of the catheter in CRI could be adopted in clinically stable patients to avoid intravascular catheter replacement.…”
Section: Introductionmentioning
confidence: 99%
“…CRIs are associated with increased mortality, morbidity, length of hospital stay and medical cost (2,11). Infection rates vary greatly, depending on the type of device, and are highest with CVCs of all types (5) The catheter should also be removed as soon as practicable, as one of the most effective and cost -efficient way of reducing the incidence of CRI.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Data on the emergence of carbapenem-resistant (CR) GNB in gastrointestinal flora and the selective capacity of carbapenem exposure are limited. We conducted a feasibility trial to evaluate the gastrointestinal selective capacity of 3 carbapenems for CR Acinetobacter baumannii, CR Pseudomonas aeruginosa, and CR Stenotrophomonas maltophilia among patients treated for healthcareassociated pneumonia.…”
Section: Gastrointestinal Selective Capacity Ofmentioning
confidence: 99%
“…Moreover, the duration of the ALT is controversial, and in vitro studies have demonstrated that shorter periods may be sufficient. 4 Also, the recent article by Sauer et al 8 suggests that a shorter ALT may be as effective as a longer-duration technique.…”
mentioning
confidence: 99%